2007
DOI: 10.1016/j.icheatmasstransfer.2007.02.002
|View full text |Cite
|
Sign up to set email alerts
|

A new procedure for power efficiency optimization in microwave ovens based on thermographic measurements and load location search

Abstract: 10In this work, a novel procedure for increasing the power efficiency of microwave ovens is presented. The procedure consists of 11 iteratively moving the sample within the microwave oven until a maximum average temperature increment is detected across the 12 sample. A new experimental set-up consisting of a multimode microwave cavity, a dielectric tracking system, a microwave power 13 source and a thermographic camera has been built and tested. Results show that it is possible to find optimal positions for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Among them samples' location, dielectric property, sample size and shape, applicators' size and its geometry, incident power and operating frequency are most important. In recent years, the effects of size, shape, applied power, operating frequency, samples' location and dielectric properties have been studied both experimentally and numerically on microwave heating efficiency and it was found out that for each different sample, varied efficiency is obtained [15][16][17][18]. This paper is an extension of work presented in ELECO 2017 conference concerning the effects of dielectric properties of the clay sample placed in the multimode applicator on the performance of microwave heating [19].…”
Section: Introductionmentioning
confidence: 99%
“…Among them samples' location, dielectric property, sample size and shape, applicators' size and its geometry, incident power and operating frequency are most important. In recent years, the effects of size, shape, applied power, operating frequency, samples' location and dielectric properties have been studied both experimentally and numerically on microwave heating efficiency and it was found out that for each different sample, varied efficiency is obtained [15][16][17][18]. This paper is an extension of work presented in ELECO 2017 conference concerning the effects of dielectric properties of the clay sample placed in the multimode applicator on the performance of microwave heating [19].…”
Section: Introductionmentioning
confidence: 99%
“…These included using external devices, such as tuners, irises and moving shorts in order to reduce reflection coefficient (Meredith 1998), coating of the material load by appropriate dielectric material for easy transfer of energy to the material inside (Monzo-Cabrera et al 2005;Dominguez-Tortajada et al 2007) or changing the position of the material inside the applicator using a moving plastic load carrier (Pedreno-Molina et al 2007). However, each of these techniques has its own limitations and implications on the overall cost of the microwave heating system and/or its complications.…”
Section: Introductionmentioning
confidence: 99%
“…For multi-mode cavity, Pedreno-Molina et al (2007) investigated the effect of load location on heating efficiency and observed that different samples with different size, permittivity and geometry produced different values of heating efficiency at each load position. Apart from these individual attempts using particular types of microwave heating applications, no thorough investigation has been made in the open literature, to our knowledge, to further explore dependence of the microwave thermal efficiency on load characteristics, irrespective of the type of material to be treated.…”
Section: Introductionmentioning
confidence: 99%
“…MW heating provides a very efficient way of producing non-contact, localized or extended heat sources by a convenient choice of the MW applicator (antenna), excitation sequence and MW selective absorption in the heated material. [11][12][13][14][15][16] Despite the huge improvements concerning magnetron power supply and magnetron efficiency, homogeneous heating of the sample still remains a problem. Currently, the engineering solutions in place for the homogenization of the MW a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%